PERILAKU DISIPLIN ANAK PADA PELAKSANAAN BELAJAR DARI RUMAH (BDR) DI RA AL-AKHYAR - Husnul Khatimah (Universitas Negeri Makassar, 2021)
This research study about the disciplinary behavior of children in the implementation of learning from home in RA Al-Akhyar. The purpose of this research was to identify : the implementation of the process of learning from home, disciplinary behavior of children while they are learning from home, and the rates of discipline of the child during learning from home. The subjects of this research is 14 children and 2 teachers in RA Al-Akhyar. The data was collected using observation, interview, and documentation. The data was analyzed by reduce data, presented data, and draw conclusion. The results of this study obtained that the disciplinary behaviour of children during the learning from home system implemented in RA Al-Akhyar is that students have developed as expected. This is proven by the achievement of six indicators of disciplinary behavior, namely : filling out the online attendance list on time, wearing uniforms during learning from home, praying in an orderly manner before starting lessons and after online learning during learning from home, trying to do the tasks that have been given during home study accompanied by parents, completing all tasks given by teachers during home study and collecting tasks on time given by teachers before online learning closes.